Federal statutes - Kozlowski, Ken (The journal of offender monitoring, 2020)
Here are federal statutory provisions from 18 U.S.C.A. §3583, 18 U.S.C.A. §3563, 18 U.S.C. § 3565, 34 U.S.C. § 60541, 34 § 11133, and 42 U.S.C.A. §5633 governing the use of GPS and other forms of electronic monitoring and 23 U.S.C.A. §164 governing repeat intoxicated drivers.